Trismus Pseudocamptodactyly Syndrome: A Sporadic Cause of Trismus - Prathima Sreenivasan; Faizal C. Peedikayil; Sumal V. Raj; Manasa Anand Meundi (Case Reports in Dentistry, 2013)
Trismus pseudocamptodactyly syndrome is a very rare autosomal dominant inherited disorder characterized by the inability to completely open the mouth (trismus) and the presence of abnormally short tendon units causing the fingers to curve (camptodactyly). Early diagnosis and management of this condition is important to prevent facial deformities in the patient. Reporting such a case is important as case reports are one of the sources of data for calculating the prevalence of rare diseases. Here, we report a case of trismus pseudocamptodactyly syndrome in an eight-year-old boy with a brief review of the literature.